2011
DOI: 10.1111/j.1600-6143.2011.03685.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Prognostic Value of Renal Resistance During Hypothermic Machine Perfusion of Deceased Donor Kidneys

Abstract: Vascular renal resistance (RR) during hypothermic machine perfusion (HMP) is frequently used in kidney graft quality assessment. However, the association between RR and outcome has never been prospectively validated. Prospectively collected RR values of 302 machine-perfused deceased donor kidneys of all types (standard and extended criteria donor kidneys and kidneys donated after cardiac death), transplanted without prior knowledge of these RR values, were studied. In this cohort, we determined the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 16 publications
11
126
5
3
Order By: Relevance
“…The observation of an inhibition of NO-dependent vasodilation after one rinse ex situ ensures that the dose used in the machine is sufficient to inhibit NOS activity during perfusion. Nevertheless, the presence of L-NAME in the machine did not alter the decrease in resistance index during perfusion observed in the present work and by others (20,(47)(48)(49). The absence of effect of L-NAME on the resistance index during MP suggests that this phenomenon is NO-independent.…”
Section: Discussioncontrasting
confidence: 36%
“…The observation of an inhibition of NO-dependent vasodilation after one rinse ex situ ensures that the dose used in the machine is sufficient to inhibit NOS activity during perfusion. Nevertheless, the presence of L-NAME in the machine did not alter the decrease in resistance index during perfusion observed in the present work and by others (20,(47)(48)(49). The absence of effect of L-NAME on the resistance index during MP suggests that this phenomenon is NO-independent.…”
Section: Discussioncontrasting
confidence: 36%
“…Similar to our study, Vries et al also found that renovascular resistance during machine perfusion did not relate to graft and patient survival [27]. In contrast, Jochmans et al has found that RT was an independent risk factor for delayed graft function and 1-year graft failure [28]. Patients in the medium GST group had worse graft survival and similar eGFR values compared to low and high groups.…”
Section: Discussionsupporting
confidence: 86%
“…Placing donor kidneys after procurement on a specialized external "pump" permits evaluation of vascular resistance flow, as well as organ viability by evaluating urine production. 23 It also notably improves outcomes by decreasing the prevalence of delayed graft function. 24,25 Because prolonged cold ischemic time (up to 48 hours) is widely accepted, en bloc kidneys procured from donor newborns can be transported easily to specialized centers willing to transplant these small organs.…”
Section: Discussionmentioning
confidence: 99%